IMPACT OF DIFFERENT LIGHT INTENSITY ON THE PRODUCTION OF THE PLANT NARCISSUS L. AND ITS FINANCIAL EFFECTS - Popović, Slobodan; Đuranović, Dragan; Laban, Bogdan; Ivić, Mladen; Jovin, Slobodanka; Nastić, Sanda; Grublješić, Željko; Popović, Vera (Economics of Agriculture, 2018)
Plant production monitoring should be conducted taking into consideration agrarian, economic and other factors. The authors of the paper point out the importance of the intensity of light on plant growing in predominantly urban growing conditions. The authors conducted an experimental research on Narcissus L. The focus was on 8 physical parameters of cultivated plants that are compared to average actual prices on the market of the Republic of Serbia. The contribution of authors is in pointing out an individual physical plant parameter with a decisive impact on its price. Narcissus L. growing under lower natural light intensity indicates that the biggest impact on plant price is that of the flower diameter (β = .555, п≤.001). Plant growing under higher light intensity has an impact on its price predominantly on the basis of the flower diameter (β=2.947, p≤.001) and stalk diameter (β = 2.947, п≤.001).